SOURCE OF FINANCES OF NON-GOVERNMENTAL ORGANIZATIONS OPERATING FOR THE IMPROVEMENT IN THE SAFETY OF THE ROAD TRAFFIC - Teresa GĄDEK-HAWLENA (Scientific Journal of Silesian University of Technology. Series Transport)
Road safety is affected by many factors, the most important one being a human. His knowledge about the correct behaviour in different situations, both the everyday ones, and the ones being a consequence of collisions or traffic accidents, is very important. Information activities in the aforementioned scope are undertaken bynon-governmental organisations which deal with the dissemination of road safety rules, first aid rules, and providing support to victims of road safety accidents. Implementation of these objectives would not be possible without the appropriate financial resources. The paper presents the sources of financing non-governmental public utility organisations whose main purpose or one of the purposes are broadly understood traffic safety measures.